Morfologi Dan Stratigrafi Desa Libungo dan Sekitarnya, Kecamatan Suwawa Selatan, Kabupaten Bone Bolango - Dhea Amelia A. Banteng; Sri Maryati; Noviar Akase (Universitas Negeri Gorontalo, 2026)
The research area is located in South Suwawa District, Bone Bolango Regency, Gorontalo Province, which is part of the North Arm of Sulawesi characterized by complex tectonic conditions. This study aims to analyze the geomorphology and stratigraphy of the research area through geological mapping and lithological interpretation. The methods used include field surveys, rock sampling, petrology analysis and spatial data analysis. The results indicate that the research area consists of two geomorphological units, namely volcanic hills and floodplain units. Stratigraphically, the area is composed of four lithological units arranged from oldest to youngest: tuff, basalt, andesite, and alluvial deposits. The distribution of these units is strongly influenced by geomorphological conditions and fluvial processes.